BCOR-CCNB3 Fusion Positive Sarcomas: A Clinicopathologic and Molecular Analysis of 36 Cases With Comparison to Morphologic Spectrum and Clinical Behavior of Other Round Cell Sarcomas. (May 2018) - Kao, Yu-Chien; Owosho, Adepitan A.; Sung, Yun-Shao; Zhang, Lei; Fujisawa, Yumi; Lee, Jen-Chieh; Wexler, Leonard; Argani, Pedram; Swanson, David; Dickson, Brendan C.; Fletcher, Christopher D.M.; Antonescu, Cristina R.
Abstract : BCOR - CCNB3 sarcoma (BCS) is a recently defined genetic entity among undifferentiated round cell sarcomas, which was initially classified as and treated similarly to the Ewing sarcoma (ES) family of tumors. In contrast to ES, BCS shows consistent BCOR overexpression, and preliminary evidence suggests that these tumors share morphologic features with other tumors harboring BCOR genetic alterations, including BCOR internal tandem duplication (ITD) and BCOR-MAML3 . To further investigate the pathologic features, clinical behavior, and their relationship to other round cell sarcomas, we collected 36 molecularly confirmed BCSs for a detailed histologic and immunohistochemical analysis. Four of the cases were also analyzed by RNA sequencing (RNAseq). An additional case with BCOR overexpression but negative CCNB3 abnormality showed a novel KMT2D-BCOR fusion by targeted RNAseq. The patients ranged in age from 2 to 44 years old (mean and median, 15), with striking male predominance (M:F=31:5). The tumor locations were slightly more common in bone (n=20) than soft tissue (n=14), with rare visceral (kidney, n=2) involvement. Histologically, BCS showed a spectrum of round to spindle cells with variable cellularity, monomorphic nuclei and fine chromatin pattern, delicate capillary network, and varying amounts of myxoid or collagenous stroma. The morphologic features and immunoprofile showed considerable overlap with other round cell sarcomas with BCOR oncogenic upregulation, that is, BCOR-MAML3 and BCOR ITD. Follow-up available in 22 patients showed a 5-year overall survival of 72%, which was relatively similar to ES (79%, P =0.738) and significantly better than CIC-DUX4 sarcomas (43%, P =0.005) control groups. Local recurrences occurred in 6 patients and distant metastases (lung, soft tissue/bone, pancreas) in 4. Seven of 9 cases treated with an ES chemotherapy regimen with evaluable histologic response showed >60% necrosis in posttherapy resections. Unsupervised clustering by RNAseq data revealed that tumors with BCOR genetic alterations, including BCOR-CCNB3, BCOR-MAML3, and BCOR ITD, formed a tight genomic group distinct from ES and CIC -rearranged sarcomas. Abstract : Supplemental Digital Content is available in the text.